Case reportPityriasis lichenoides-like secondary syphilis and neurosyphilis in a HIV-infected patient - Pastuszczak, Maciej; Woźniak, Wioletta; Jaworek, Andrzej K.; Wojas-Pelc, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Papulo- and vesiculo-necrotic lesions are rare manifestations of secondary syphilis. Until now it has been described only in HIV-infected patients with advanced stages of immunosuppression. This case report describes an unusual case of PLEVA-like syphilis in a 33-year-old man with newly diagnosed HIV infection. Despite that the CD4 cells level and viral load did not indicate the advance stage of immunosuppression, the unusual manifestation of syphilis and neurosyphilis occurred. The presented case indicates the need for HIV screening in every patient with syphilis especially when the clinical manifestation is unusual. Importance of syphilis testing in every case with atypical rashes should be also highlighted.